Eksistensi Hukum Islam dan Prospeknya di Indonesia - A. Malthuf Siroj (Universitas Nurul Jadid, 2018)
Indonesia as one of the most populated-by-Muslim country has a long historical experience in implementing Islamic law. In each era, the practice of Islamic law differs one another due to the legal politics which influence it. Prior to the Dutch colonialism, Islamic law was prevalent among Muslims with political support from the royal kingdom of Islam such as in Aceh, Palembang, Banjarmasin, Banten, Demak, Jepara, Tuban, Gersik, Ampel and Mataram. Islamic law grew and developed in the midst of society beside adat law. In the Dutch colonial era the policy of the colonial government against Islamic law had its ups and downs in line with the legal theory that emerged at the time. On the one hand, it tends to be accommodative, while confrontational on the other hand. In the era of independence the position of Islamic law became stronger with the enactment of the 1945 Constitution which guaranteed the right of every citizen to embrace religion and practise religious law. In the New Order era, several laws have been enacted, which strengthened the position of Islamic law, especially the Islamic civil law. This tends to develop in the Reform era, marked by strengthening Muslim aspirations and regional autonomy. Consequently, the Islamic law is increasingly practised, though still limited in the field of civil law and Islamic economics. The enforcement of Islamic criminal law in Indonesia still encounter many obstacles both conceptually and legally. This article will examine the existence and the prospect of Islamic law in Indonesia by observing its strengths, weaknesses, opportunities and challenges.